2004
DOI: 10.1038/sj.bjc.6602001
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of radiotherapy combined with gemcitabine for locally advanced pancreatic cancer

Abstract: Gemcitabine has been reported to be a potent radiosensitiser in human pancreatic cell lines. This study was conducted to evaluate the efficacy and toxicity of radiotherapy combined with gemcitabine for locally advanced pancreatic cancer. In all, 42 patients with pancreatic cancer that was unresectable but confined to the pancreatic region were treated with external-beam radiation (50.4 Gy in 28 fractions over 5.5 weeks) and weekly gemcitabine (250 mg m À2 , 30-min infusion). Maintenance gemcitabine (1000 mg m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 26 publications
3
43
1
Order By: Relevance
“…We summarised recent phase II trials on chemoradiotherapy combined with gemcitabine alone or gemcitabine plus cisplatin in locally advanced pancreatic cancer (Table 4) (de Lange et al, 2002;Li et al, 2003;Okusaka et al, 2004;Wilkowski et al, 2004;Magnino et al, 2005;Haddock et al, 2007). Compared with the recent phase II study by Haddock et al, although the dose and cycle differed from our study, 24.4% ORR and 16.7 months median survival time of our study showed favourable results.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…We summarised recent phase II trials on chemoradiotherapy combined with gemcitabine alone or gemcitabine plus cisplatin in locally advanced pancreatic cancer (Table 4) (de Lange et al, 2002;Li et al, 2003;Okusaka et al, 2004;Wilkowski et al, 2004;Magnino et al, 2005;Haddock et al, 2007). Compared with the recent phase II study by Haddock et al, although the dose and cycle differed from our study, 24.4% ORR and 16.7 months median survival time of our study showed favourable results.…”
Section: Discussionmentioning
confidence: 44%
“…On the basis of the most conservative assumption of a 30% survival rate at 1 year (null hypothesis) in historic controls with locally advanced pancreatic cancer (Okusaka et al, 2004), an increase of 50% or more (alternative hypothesis) could be shown with a power of 80% by investigating a sample size of at least 35 patients (a ¼ 0.05, one-sided test) (A'Hern, 2001). Overall survival and TTP were analysed using Kaplan -Meier method with 95% confidence intervals (CIs).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations